Under the magnifying glass: critical moments in virtual exchange - Judit Háhn; Katarzyna Radke; Ivonne Dekker (University of Groningen Press, 2022)
Virtual Exchange (VE) is a form of experiential learning that relies heavily on learning-by-doing and reflection. The present study draws on visual data comprising students' perceptions of critical learning incidents presented under an imaginary magnifying glass. To complete this project-closing reflective activity, the students had to describe a critical moment that they had experienced during VE and present it in a visual form. Data was collected longitudinally, in three projects (2019, 2020, and 2021) that followed the same pedagogical design and focused on the theme of tourism. The collaborating universities were from three countries: Poland, Finland, and the Netherlands. We used the methods of qualitative content analysis and social semiotic analysis to investigate the students' reflections. The findings show that the most frequently expressed themes were related to participation in the first meeting, joint production, use of a foreign language, and adaptation to change. The study contributes to a better understanding of the role of multimodal reflection in VE.